Análisis del comportamiento de la canasta básica del cantón Guayaquil, Ecuador - Astudillo Muñoz, Antony Andres (2022)
The development of this research had the general objective of analyzing the basic basket of the Guayaquil canton, period 2016-2020. The methodology used is a mixed approach with a quantitative and qualitative study; The scope of the study was descriptive, so statistical bases from the INEC and the Ministry of Labor were used, Tables and figures were developed that make it possible to know this behavior of the basic family basket. Most of the results are related to the social, educational level and salary policies. Which leads to an understanding that in 2016 the variation of the Consumer Price Index (IPC) was 1.58, the highest until 2020. As of 2017, the study has shown that there is a slight decrease in the variation in the Consumer Price Index (IPC) until 2018. In 2019, the new adjustment proposed by the Government of Lenin Moreno to face the fiscal deficit and indebtedness, directly affects public spending, removing the subsidy on extra gasoline and diesel. Not in accordance with these measures, those affected went out to protest in the streets, the reduction of vehicular flow on the main roads where vehicles circulate transporting essential products were obstructed by various groups of protesters. After reaching an agreement, in 2020 the COVID-19 pandemic begins due to confinement, many companies went bankrupt, cut staff and others took other ways of working. Despite this adversity, the variation in the IPC in 2020 is 0.20.